Utilization of Gamma Irradiated Aspergillus niger to Improve Oil Palm by-Product Digestibility - Teguh Wahyono; Nana Mulyana; Putri Amanda; Siti Nurbayti; Suharyono Soharyono (Buletin Peternakan, 2018)
This study was conducted to determine the effect of fermentation using irradiated A. Niger on in vitro rumen fermentation characteristics of oil palm by-products. Completely randomized design with eight treatments and four replications was applied in this experiment. The treatments were kernel shell (CK), palm frond (PKS), oil palm empty bunches (TKKS), CK+PKS+TKKS (mix), fermented kernel shell (CKF), fermented palm frond (PKSF), fermented oil palm empty bunches (TKKSF) and fermented mix (mixF). The results showed that fermentation process reduced NDF content of PKS and TKKS by 7.42 and 7.09% respectively. Fermentation also decreased ADF content of TKKS by 7.35%. Maximum total gas production (a+b) of TKKS and mix sample decreased after fermentation process (P<0.05) by 52.92 and 35.60% respectively. Total VFA production increased on kernel shell and palm fronds samples after fermentation process (P<0.05) however CO2:CH4 ratio tended to be decrease. The conclusion of this study was the fermentation process by irradiated A. niger improved rumen fermentation characteristics of oil palm by-products, however more appropriate strategy is needed to reduce CH4 emissions.